Spine deviations in elite rhythmic gymnasts: Relationships with the bone status and the characteristics of training - Flora, D.; Portier, H.; Courteix, D. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
A prevalence of spine deviations have been reported in young female rhythmic gymnasts (RG). The causes of such pathology are not yet known and whether these problems are under the effects of a specific training and /or due to the body characteristics of the gymnasts remains to be clarified. Different theory have been discussed, but none of them has been definitely proved. Debates concerning the primary and the secondary changes in the deformed spines still continue, but to little avail. This helplessness is reflected in the accepted"multifactorial origine" of idiopathic scoliosis (Tanchev). Objective: To analyze the spine deviations of rhythmic gymnasts and to check their relationships with the body characteristics and bone status. Methods: Thirty girls aged 11 to 17 years belonging to the French national elite team participated in this study. Body weight, height and body composition were measured. Regional and total body bone mineral density (BMD g/cm2), bone mineral content (BMC g), bone area (BA; cm2) fat mass (g) and lean mass (g) were measured by dual-energy X-ray absorptiometry (DXA; Hologic Delphi W). The analyze was made at the whole body and the lumbar spine (L1 - L4). The Instant Vertebral Imaging software allowed the analysis of the vertebral deformity in antero-posterior and lateral plans. The kyphotic curves, lumbo-sacral angle and lumbar curves were measured in each subjects. The Cobb angle was assessed for the subjects presenting a deviation in frontal plan. The examination included also the duration, intensity and specific element of rhythmic gymnastic training using a questionnaire. Results: Among the RG trainees, 13 had scoliotic curves higher then 10°, representing an incidence of 43.3% vs 1.5% that was established in a normal French population (Table 1). All the subjects presented spine deviations, either in the sagittal or in the frontal plan, which were significantly different than those observed in a normal population (Table 2). Neither the antropometric values nor BMD and BMC values correlate with the degree of curves. The age and the years of practice were not linked to the severity of the spine pathologies. Conclusion: The main findings of this study was that a large percentage of the gymnasts presented spine deformations, either in the sagittal or in the frontal plan. Our observations show that the bone status does not explain the spine deviation in such a highly-trained population. These deviations are not linked to the body characteristics of the subjects therefore we could suggest that the specifics of gymnastics training may contribute to the pathogenesis of the gymnasts` spines.